Rapid and accurate evaluation of vaporized hydrogen peroxide on the efficiency of disinfection, using a sensitive dual-channel laser scanning cytometerHighlights - Meng Chen; Jiancheng Qi; Yaohua Du; Zhi Cheng; Tianyu Cai; Chao Li (Elsevier, 2021)
Vaporized hydrogen peroxide (VHP) is a highly active disinfectant, and VHP decontamination systems have been widely applied in hospitals, microbiological laboratories, and pharmaceutical industries. However, the decomposition of VHP into non-toxic by-products is essential. Evaluation of the disinfection efficacy of VHP is crucial to ensuring the reliability of VHP disinfection and controlling microbial contamination. In this study, a rapid and sensitive strategy is proposed to evaluate the efficacy of VHP in surface disinfection by detecting the survived and killed bacteria from VHP-exposed biological indicators (BIs). A dual-channel solid-phase cytometer is designed, and fluorescent dyes are used as indicators to automatically and accurately distinguish live cells from dead cells in the mixtures of bacteria. To verify the availability and effectiveness of the laser scanning cytometry, experiments on its application in estimating the efficacy of VHP disinfection practice have been carried out in this study, and its estimation effect compared with that of the traditional plate counting method. Results show that the proposed assay might distinctly identify live or killed cells labeled by green and red fluorescent dyes and examined the disinfection efficacy in 30 min by calculating the bactericidal rate. Compared with the plate counting method, the proposed approach is accurate and practical, with an average detection efficiency of 98.47% ± 1.55%. Moreover, an excellent correlation between the concentrations of B. subtilis var niger (ATCC 9372) measured by the proposed detection system and by the plate counting method is noticed (R2 = 0.9971), indicating that this approach had advantages in the detection of trace microorganisms. To summarize, the proposed strategy appears practical and significant in many fields in which microbial counting and identification are required.